Populārāko skolvadības sistēmu salīdzinājums un ieviešana vispārizglītojošā skolā Latvijā - Stucka, Arnis (Latvijas Universitāte, 2017)
Darbā tika pētītas dažādas skolvadības sistēmas un to popularitāte Latvijā. Tika aplūkotas vairākas skolvadības sistēmas definīcijas. Tika apskatītas konkrētas sistēmas Moodle, E-klase, ĢIS un Mykoob. Tika aplūkota labās prakses piemēru kopa, kas jāievēro, veidojot skolvadības sistēmas. Praktiskajā daļā tika ieinstalēta un praksē pārbaudīta Moodle sistēma vispārizglītojošā skolā. Tika izpētīti Moodle sistēmas uzturēšanas un ieviešanas dažādi aspekti. Rezultātā tika iegūta autora izveidota labās prakses piemēru kopa skolvadības sistēmas ieviešanai skolā, balstoties uz Moodle sistēmas ieviešanas piemēra.

In this paper “The most popular school management system comparison and implementation in comprehensive school in Latvia” a variety of learning management systems and their popularity in Latvia were studied. Several definitions of learning management system were considered. The Moodle, “E-Klase” and Mykoob systems where analized. The possible examples of best practice guidelines to be followed when deploying a learning management system for school were analized. In the practical part the Moodle system was installed in a comprehensive school and was tested with high school students. Moodle system maintenance and implementation of various aspects where explored. In the result the set of best practices for implementation of school management system where obtained by the author based on the implementation example of Moodle platform.
The most popular school management system comparison and implementation in comprehensive school in Latvia
Keywords: Datorzinātne; Skolvadības sistēma; Moodle; E-klase; Mykoob